Genetic analysis and association detection of agronomic traits in maize genotypes - Seyyed Mohammad Sadegh Hosseini; Mohammadreza Shiri; Khodadad Mostafavi; Abdollah Mohammadi; Seyyed Mehdi Miri (Scientific Reports)
Abstract In maize breeding, enhancing yield through genetic insights is crucial yet challenged by the complex interplay of agronomic traits. This study utilized a diallel mating design involving nine advanced early maize lines to dissect the genetic architecture underlying key agronomic traits and their impact on yield. Over two consecutive years (2018–2019 and 2019–2020), 36 hybrids derived from these lines were grown across two locations, Karaj, Alborz, Iran and Kermanshah (2019–2020), Iran, in a randomized complete block design with three replications. The study aimed to evaluate the general combining ability of the parental lines and the specific combining ability of their hybrids, alongside the mutual influences of critical traits on yield. The analysis of variance revealed significant differences at 1% and 5% probability levels among the hybrids for all traits studied, indicating substantial genetic variability. Diallel analysis suggested that both additive and non-additive genetic effects are crucial in controlling traits such as kernel yield, kernel rows, kernel in row, 1000 kernel weight, plant height, ear height, kernel moisture, and ear wood. Additive effects, as indicated by the Baker’s ratio, predominated for these traits. Among the parental lines, KE 79,017/3211 demonstrated the strongest general combining ability for kernel yield. Hybrids K 1264/5–1 × KE 76,009/311, KE 77,005/2 × KE 75,016/321, KE 77,008/1 × KE 77,004/1, and KE 77,008/1 × KE 79,017/3211 exhibited significant and positive specific combining ability effects for kernel yield, highlighting their potential in yield-enhancing breeding programs. Correlation analysis showed no significant association between KY*KIN with the KY*KW. However, there were weak positive correlations between KY*KR with other traits such as KY*PH, KY*KR, and KY*EH. The biplot analyses identified genotypes 4, 12, and 31 as superior across various trait combinations. Genotype 12 emerged as notably high-yielding based on average tester coordinates. Using the multi-trait stability index and imposing a selection pressure of 25%, genotype 10 was ranked highest, followed by genotypes 9, 13, 11, 1, 2, and 16, which were considered the most stable and ideal across all evaluated traits. This comprehensive study underscores the importance of both general combining ability and specific combining ability in maize breeding and highlights specific genotypes and hybrid combinations with promising traits for yield enhancement.